Kepentingan Galeri Seni Visual Swasta dalam Konteks Masyarakat terhadap Kelestarian Kesenian di Kuching - Wong, Neng Lee (2021)
Private art gallery has become the major platform for artists to showcase their art works and acts as an intermediary between the artists and society. However, it is observed that private art gallery is still getting less exposed in the local society. Therefore, this research sought to find out the importance of private art galleries, the effectiveness of private art galleries and problems that plaguing private art galleries in Kuching as well as ways to promote private art galleries to the public. Combination of qualitative and quatitative approaches has been used to carry out the research. The findings revealed that there are few ways ought to be carried out to increase the use of the private art galleries and realize the importance of private art galleries in Kuching. The society, artists, government, private sectors and NGOs play vital roles in the development of private art galleries in Kuching by orginasing more exhibitions, carrying out more art activities and support local art activities. Hopefully this research will play a role as a guideline to help reseachers to do futher research in future. Furthermore, hopefully public will visit private art galleries more often and involve actively in fine arts activities.